Biochemical characterisation of Pfj2, a Plasmodium falciparum heat shock protein 40 chaperone potentially involved in protein quality control in the endoplasmic reticulum - Afolayan, Omolola Folasade (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2013)
Plasmodium falciparum is a protozoan parasite that causes a severe form of malaria, a mosquito-borne infectious disease in humans. P. falciparum encodes a number of proteins to facilitate its life-cycle, including a type II heat shock protein 40 (Hsp40), Pfj2. Pfj2 shows a degree of homology to human ERdj5, a resident protein of the endoplasmic reticulum (ER) that promotes protein quality control by facilitating the degradation of misfolded proteins. The overall aim of this study was to further understand the function of Pfj2 in the P. falciparum cell by characterising it biochemically. A bioinformatic analysis of Pfj2 was carried out to enable the identification of a potential ER signal sequence and cleavage site. Furthermore, an analysis of Pfj2 protein sequence was performed to compare domain similarities and identities with typical type II Hsp40s namely, human ERdj5, S. cerevisiae Sis1, human Hsj1a and human DnaJB4. The method used included the insertion of the codon-optimised coding sequence for the processed ER form of Pfj2 into the prokaryotic expression vector, pQE30, to enable overproduction of a histidine-tagged protein. A 62 kDa His₆-Pfj2 was successfully expressed in Escherichia coli and purified using denaturing nickel affinity chromatography. ATPase assays were performed to determine the ability of His₆- Pfj2 to stimulate the chaperone activity of the ER Hsp70, also called immunoglobulin binding protein (BiP). Initial studies were conducted on readily available mammalian His₆-BiP as a control, which was shown to have an intrinsic activity of 12.07±3.92 nmolPi/min/mg. His₆- Pfj2 did not stimulate the ATPase activity of mammalian His₆-BiP, suggesting that it either could not act as a co-chaperone of mammalian His₆-BiP (specificity), or it required a misfolded substrate in the system. Therefore, ongoing studies are addressing the interaction of Pfj2 and misfolded substrates with P. falciparum BiP. The results of these studies will further our understanding of a poorly-studied parasite chaperone that represents a potential drug target for development of novel strategies for the control of a serious human disease
Keywords: Plasmodium falciparum; Endoplasmic reticulum; Heat shock proteins; Malaria; Mosquito-borne infectious disease